2010
DOI: 10.1073/pnas.1005259107
|View full text |Cite
|
Sign up to set email alerts
|

Regional differences in cellular mechanisms of adipose tissue gain with overfeeding

Abstract: Body fat distribution is an important predictor of the metabolic consequences of obesity, but the cellular mechanisms regulating regional fat accumulation are unknown. We assessed the changes in adipocyte size (photomicrographs) and number in response to overfeeding in upper-and lower-body s.c. fat depots of 28 healthy, normal weight adults (15 men) age 29 ± 2 y. We analyzed how these changes relate to regional fat gain (dual energy X-ray absorptiometry and computed tomography) and baseline preadipocyte prolif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
252
2
7

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 331 publications
(283 citation statements)
references
References 40 publications
13
252
2
7
Order By: Relevance
“…Lower body fat compartments of obese women contain more adipocytes than those of lean women, whereas obesity is not related to cell number in lower-body compartments of men (560). Consistent with these findings, a longitudinal study performed in men and women showed that adipocyte progenitor cells of the lower body fat compartments can develop rapidly into mature adipocytes in response to overfeeding and that this response depends partially on sex of the participant and baseline adipocyte size (563). These results indirectly suggest that during weight gain, lower-body adipose tissues tend to expand through hyperplasia in women, but through hypertrophy in men (560,563).…”
Section: B Adipocyte Sizementioning
confidence: 59%
“…Lower body fat compartments of obese women contain more adipocytes than those of lean women, whereas obesity is not related to cell number in lower-body compartments of men (560). Consistent with these findings, a longitudinal study performed in men and women showed that adipocyte progenitor cells of the lower body fat compartments can develop rapidly into mature adipocytes in response to overfeeding and that this response depends partially on sex of the participant and baseline adipocyte size (563). These results indirectly suggest that during weight gain, lower-body adipose tissues tend to expand through hyperplasia in women, but through hypertrophy in men (560,563).…”
Section: B Adipocyte Sizementioning
confidence: 59%
“…6 Decreased preadipocyte frequency and proliferative capacity is associated with obesity and metabolic disease in some, 6,14,[16][17][18] but not all 19 studies. These conflicting literature may result from patient heterogeneity, wide intrinsic variability in human preadipocyte frequency, 19,20 and different techniques used to quantify preadipocytes. One study demonstrated a relationship between decreased preadipocyte number and DM restricted to VAT, 16 similar to our findings and consistent with the well-established stronger association of metabolic disease with VAT.…”
Section: Discussionmentioning
confidence: 99%
“…2), which some studies have shown occurs primarily in the visceral fat depots of mice (Kim et al, 2014;Wang et al, 2013). Other studies have shown an association between hyperplasia and subcutaneous fat depots (Tchkonia et al, 2013), with a higher capacity for adipogenesis observed in femoral rather than in abdominal subcutaneous depots in humans (Tchoukalova et al, 2010). However, a study by van Beek and colleagues demonstrated that pgWAT in mice has a limited capacity to store lipids, which is reached when mice achieve an average body weight of 40 g (van Beek et al, 2015).…”
Section: Metabolic Risk Is Associated With Individual Adipose Tissue mentioning
confidence: 99%